Between the Protection and Humanity: The Implementation of Ultimum Remedium Principle in Immigration Cases - Bahari, Alamsyah (Indonesian Journal of Advocacy and Legal Services, 2020)
Global population mobility has an impact on legal aspects, especially in the case of immigration matters. Increased mobility of migration flows also has various impacts, not only positive but also negative impacts, for example changing the pattern of crime from domestic crime to transnational crime, from individual crime to group crime, from unorganized crime to organized (organized crime). Various administrative and criminal sanctions are applied to many immigration offenders. This paper examines in depth the application of the principle of ultimum remidium in criminal law for criminal acts of immigration in Indonesia. This study aims to find out and understand how the ultimum remedium principle is applied in Law Number 6 of 2011 concerning Immigration. In addition, this study also aims to find out and understand the factors that cause Immigration Officers to use Administrative Sanction Acts or Criminal sanctions in Law Number 6 of 2011 concerning Immigration, as well as to know and understand Immigration law enforcement practices in Law Number 6 of 2011 concerning Immigration in Indonesia. This research has confirmed and underlined that the application of administrative sanctions in the form of deportation and fines will complete the immigration legal process quickly, simply and at a modest cost and applying relatively high fines can benefit the country, hence the benchmarks for the principle of ultimum remedium can be applied in the Law Law No. 6 of 2011 concerning Immigration.